NEONATAL JAUNDICE IN HYPERBILIRUBINEMIC INFANTS - Fadliyah, Lailatul; Mardhika, Amellia; Eka Sarofah; Sari, Dita Novita (Journal of Vocational Nursing, 2022)
Introduction: Hyperbilirubinemia is a problem that often occurs in newborns. In pathological conditions, infants experience jaundice throughout the body or degrees three to six experiencing hyperbilirubinemia > 12 mg/dl. Complications of kernicterus where brain cells are damaged, are characterized by seizures, decreased consciousness and can end in death. East Java Health Profile 2013, neonatal icterus neonatorum death ranks third. Methods: This research uses a case study design. Data collection from assessment to nursing evaluation was carried out in the neonatal room of Dr. Soegiri Lamongan Hospital in November 2019. Clients were treated in hospital for three to five days. Data collection techniques using interviews, observation, and documentation. Data analysis was carried out using narrative analysis based on analysis of relevant facts and theories. Results: In the assessment, the baby experienced symptoms of jaundice, yellow mucous membranes, yellow skin, and yellow sclera. Intervention and implementation were observing the degree of jaundice, vital signs, intake output, signs of dehydration, and phototherapy. Health education on breastfeeding and collaboration in drug administration. Conclusions: There is a match between theory and cases, there is a decrease in the degree of jaundice. The reference from this study is that nurses are able to provide health education on breastfeeding, do phototherapy and be able to detect the incidence of jaundice early in infants so there is no kern icterus and other complications.